Factors affecting individual investment decision on residential properties / Muhammad Farhan Ramlan and Siti Nurulain Zulkarnain - Ramlan, Muhammad Farhan; Zulkarnain, Siti Nurulain (Faculty of Business and Management, Universiti Teknologi MARA, 2013)
The purpose of this study is to determine factors affecting individual investment decision on residential properties. The residential property price in Malaysia will keep increasing from month to month but at a slower rate which it gradually increase. This study is to identify the relationship between independent variables which are investor’s behaviour, investor’s knowledge and microeconomic factor to the dependent variable which is individual investment decision on residential properties. This study also is to determine the most significant factor that affecting individual investment decision on residential properties. This study were found that all the independent variables have significant and positive relationship with the dependent variables and investor’s knowledge is most significant factor that affecting individual investment decision on residential properties. Further research is proposed to determine the others factor such as macroeconomic, socioeconomic and demographic factors that can be potential factor that affecting individual investment decision on residential properties.